CGIAR Climate Change Impact Platform Bi-Monthly Newsletter, Edition 2, March-April 2024 - Mukherji, Aditi; Edward-Uwadiale, Regina (CGIAR Climate Change Impact Platform, 2024)
Welcome to edition 2 of our Climate Impact Platform Bi-monthly newsletter, where we will showcase Platform activities, share impactful climate stories from CGIAR Research Centers, bilateral projects, and ongoing Initiatives, feature CGIAR climate scientists, and keep you informed of upcoming events and key moments.